Collapsing time: LGBTQ+ rights in Northern Ireland, A Queer Céilí at the Marty Forsythe. Issue 1 (1st December 2020) - Durrer, Victoria; Grant, David
This article examines Kabosh Theatre Company's production of Dominic Montague's A Queer Céilí at the Marty Forsythe, in Belfast, Northern Ireland, during its first run in March 2019. Based on archival research and personal accounts of a weekend surrounding the October 1983 National Union of Students Lesbian and Gay Conference in Belfast, the play depicts a moment of lesbian and gay activism largely neglected in critical and popular historical accounts of the period known as the 'Troubles' (1968‐98). Through observation of rehearsals and performances as well as in-depth interviews with audiences and artists, we argue that the play's situation in the venue, where many of the events portrayed originally took place, and the use of archival and found photographic imagery as key scenic elements create a sense of 'collapsed time' that brings the past into dialogue with the present and future, particularly regarding the relationship of LGBTQ+ rights to societal reconciliation.